Pengaruh Geometri Jalan Tambang Terhadap Alat Angkut Kegiatan Pengupasan Overburden Penambangan Batubara PT Tata Bara Utama di Kabupaten Bayung Lencir, Provinsi Sumatera Selatan - Nabil Zulfa Maulana; Zaenal; Indra Karna Wijaksana (UNISBA Press, 2022)
Abstract. PT Tata Bara Utama is a contractor from PT Manggala Alam Lestari which is saved to overcome Over Burden (OB) with a target of reaching 288,200 BCM in one month. The company's production target was not achieved due to unfavorable road geometry conditions. This is because there are several mine road geometries that do not meet the standards of Ministerial Decree 1827 k/30/m/2018, thus hampering the production of conveyances. The conveyance used is the 745 articular dump truck. The conveyance operates from the front of the work to the disposal with a distance of 2700 m. Productivity of hauling equipment is strongly influenced by the geometry of the mine road, so that the 13 segments of the mine road geometry do not meet the standards of Kepmen 1827 and must be repaired immediately. In the results of the study, there were several segments of the mining road that were not in accordance with these standards. There are 3 segments on the straight road and 5 segments on the bend road that do not meet the standards in the geometry of the mining road, but the grade (slope of the road) has met the standards of Kepmen 1827, and there are still some segments of the embankment that do not meet these standards. This means that the productivity produced in each unit of conveyance is 49.67 BCM/hour so that the production of PT Tata Bara Utama reaches 196,700 BCM/Month while the production target is 288,200 BCM, so the production target is not achieved. Therefore, it is necessary to do reconstruction so that the desired production target of the company will be achieved. This means that the greater the cycle time value on the conveyance, the lower the productivity so that production is not reached. Abstrak. PT Tata Bara Utama merupakan perusahaan kontraktor dari PT Manggala Alam Lestari yang bertugas untuk mengupas Over Burden (OB) dengan target mencapai 288.200 BCM dalam satu bulan. Target produksi perusahaan tidak tercapai dikarenakan kondisi geometri jalan yang tidak mendukung. Hal ini terdapat beberapa geometri jalan tambang belum memenuhi standar Kepmen 1827 k/30/m/2018 sehingga menghambat kerja produksi alat angkut. Alat angkut yang digunakan yaitu articular dump truck 745. Alat angkut beroperasi dari front kerja menuju disposal dengan jarak 2700 m. Produktivitas alat angkut sangat dipengaruhi oleh geometri jalan tambang, sehingga dari 13 segmen geometri jalan tambang belum memenuhi standar Kepmen 1827 dan harus segera diperbaiki. Pada hasil penelitian terdapat beberapa segmen jalan tambang yang belum sesuai dengan standar tersebut. Ada 3 segmen pada jalan lurus dan ada 5 segmen pada jalan belokan yang belum memenuhi standar pada geometri jalan tambang, akan tetapi grade (kemiringan jalan) telah memenuhi standar Kepmen 1827, dan tanggul masih ada beberapa segmen yang belum memenuhi standar tersebut. Hal ini produktivitas yang dihasilkan pada tiap unit alat angkut sebesar 49,67 BCM/jam sehingga produksi PT Tata Bara Utama mencapai 196,700 BCM/Bulan sedangkan target produksi 288.200 BCM maka target produksi tidak tercapai. Maka dari itu perlu dilakukan rekontruksi agar target produksi yang diinginkan perusahaan akan tercapai. Hal ini semakin besar nilai cycle time pada alat angkut akan semakin kecil produktivitasnya sehingga produksi tidak tercapai.